The Anatolian Journal of Cardiology 2022
DOI: 10.5152/anatoljcardiol.2022.1597
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulant Use and Long-Term Follow-Up Results in Patients with Non-valvular Atrial Fibrillation in Turkey AFTER-2 Study

Abstract: Background : The aim of this study was to investigate the frequency of oral anticoagulant drugs and time in therapeutic range in patients receiving warfarin in addition to the epidemiological trial of non-valvular atrial fibrillation previously conducted in Turkey (The Atrial Fibrillation: Epidemiological Registry trial). Furthermore, the prevalence of major adverse events and mortality rates of the patients were evaluated during the long-term follow-up period. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Moreover, it has been shown that the clinical effectiveness of VKA decreases sharply as TTR falls below 65% compared to antiplatelets [7]. In the AFTER-2 study, the mean TTR of the patients was 40%, and only 31.4% of the patients' TTR values were in the effective range [13]. INR measurements should be done more frequently to improve VKA management, but this implies additional costs for laboratory resources [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that the clinical effectiveness of VKA decreases sharply as TTR falls below 65% compared to antiplatelets [7]. In the AFTER-2 study, the mean TTR of the patients was 40%, and only 31.4% of the patients' TTR values were in the effective range [13]. INR measurements should be done more frequently to improve VKA management, but this implies additional costs for laboratory resources [16].…”
Section: Discussionmentioning
confidence: 99%
“…The study is a subgroup analysis of the trial: "Oral Anticoagulant Use and Long-Term Follow-Up Results in Patients with Non-valvular Atrial Fibrillation in Turkey AFTER-2" [13].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we found that the most common comorbid condition in patients was CKD. 13 In addition, we had 327 (12.6%) patients with GFR ≥ 90, 479 (18.5%) patients with 60 ≤ GFR < 90, 1141 (44%) patients with 30 ≤ GFR < 60, 499 (19.3%) patients with 15 ≤ GFR < 30, and 146 (5.6%) patients with GFR < 15. Among our patient population, rivaroxaban was the most commonly used NOACs, followed by dabigatran.…”
mentioning
confidence: 99%
“…In the latest issue of The Anatolian Journal of Cardiology , I have read with keen interest the article by Güzel et al 1 showing the current anticoagulation practice among atrial fibrillation (AF) patients in Turkey. In The Atrial Fibrillation: Epidemiological Registry (AFTER)-2 registry involving 2592 outpatients with AF at a mean age of 69 years, the majority of whom represented the high-risk group, the authors reported a marked increase in the proportion of anticoagulated individuals in recent years up to almost 73%, with 42% on direct oral anticoagulants (most commonly on rivaroxaban) and 31% on warfarin (unfortunately, with a low time in therapeutic range of 40%).…”
mentioning
confidence: 99%
“…In The Atrial Fibrillation: Epidemiological Registry (AFTER)-2 registry involving 2592 outpatients with AF at a mean age of 69 years, the majority of whom represented the high-risk group, the authors reported a marked increase in the proportion of anticoagulated individuals in recent years up to almost 73%, with 42% on direct oral anticoagulants (most commonly on rivaroxaban) and 31% on warfarin (unfortunately, with a low time in therapeutic range of 40%). 1 From the practical perspective, right dosing regimens of nonvitamin K antagonist oral anticoagulants (NOACs) are of key importance to avoid common and dangerous underdosing as well as infrequent overdosing. 2 …”
mentioning
confidence: 99%